Clinical pharmacology - Brown, Morris J; Sharma, Pankaj; Mir, Fraz A; Bennett, Peter N (Elsevier, 2019)
The twelfth edition of this long-established textbook of clinical pharmacology (first published in 1960) continues its fine tradition of balancing science and practice for improved evidence-based drug therapy and good prescribing in therapeutic settings increasingly complicated by intercurrent disease and polypharmacy.